Photocatalytic hydrogen production from H2S using nanostructured CNT blended CdZnS/Fe2O3 thin film on glass substrate - Raja, M. Anthony; Vijayarengan, Preethi; Pal, Yash; Nalajala, Naresh; Gopinath, Chinnakonda (Journal of Physics Conference Series, 2020)
<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A co-precipitation method was employed to prepare the CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst. Using the powder photocatalyst, the thin film of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst over a glass substrate was prepared using the drop-casting method. The obtained thin film was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive X-ray analysis (EDAX), photoluminescence (PL), and hydrogen production activity studies in order to obtain information on their structural, morphology, chemical composition, optical and hydrogen production efficiency. The hydrogen production activity of catalyst or effective conversion of H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S into hydrogen (H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) and sulfur (S) using thin-film photocatalyst was evaluated using a simulated sulfide solution. The results showed that 1 mg of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst coated as thin film over glass substrate (4.69 cm<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) showed the highest hydrogen production value of 3180 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">; compared to that of 1 mg CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> powder of 2510 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. From the above results, it is concluded that the thin film form of photocatlyst produced more hydrogen than the powder form. This is attributed to the effective charge separation and increased specific surface area in thin film photocatalyst.

Thin-film approach for scalability and enhancement of solar hydrogen production with CNT integrated Ce-doped-TiO2 composite in direct sunlight - Vijayarengan, Preethi; Maria, Anthony Raja; Ashadevi, K. S.; Nalajala, Naresh; Gopinath, Chinnakonda S. (Materials Today Catalysis, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Solar hydrogen production by photocatalysis has long been considered as an important energy option. Whichever photocatalyst succeeds, methods should be available to scale-up in a most sustainable and cost-effective manner, and the present work addresses this specific issue. In the present study, Ce-doped in the TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> lattice (Ce-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) and the same integrated with CNT (CNT-Ce-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">; (CCT)) composite was synthesized and characterized. Current study demonstrates the synergistic integration of Ce-TiO₂ as a light absorber and charge generator with CNTs as efficient charge separation at heterojunctions as well as charge transporter in a thin-film configuration (lab-scale (4.7 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">), bench-scale (500 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">)). Improved H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> generation under direct sunlight demonstrated in thin film form, than in particulate suspension, is attributed to efficient light absorption, particularly for electron-hole pair separation and their dispersion to redox sites. Additionally, the role of the binder is highlighted for improving H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> yield and the sustainability of the thin-film form of photocatalyst. ∼200 mg (1 g) CCT coated over 500 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> (2500 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) photocatalyst produced 21.6 mmol/h (102 mmol/h) H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> in sunlight. Present results provides a proof of concept that the thin film form of photocatalyst displays, at least 10 times, higher H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> yield than its powder counterpart, depending on the measurement conditions. A non-linear enhancement in H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> yield with small and large area thin-film indicates complex underlying factors and highlights the scope for further improvements.